Chitosan–gelatin enhanced antibacterial and biological properties of PLA and PGA braided threads for juvenile pseudomyopia treatment. Issue 17 (September 2021) - Fu, Shaoju; Zhang, Peihua
Polylactic acid (PLA) and polyglycolide acid (PGA) have been the most widely used biomedical materials in the acupoint catgut-embedding therapy (ACET) fields. However, a lack of antibacterial and biological properties is a definite obstacle that hinders its further application in juvenile pseudomyopia treatment. Here, four different kinds of PLA and PGA threads were fabricated, and were then modified using chitosan–gelatin coating method. Afterwards, PLA and PGA braided threads were fully characterized with respect to structure, mechanical and biological properties. The results showed that the surface roughness of PLA and PGA had been greatly improved; FT-IR analysis proved the existence of chitosan and gelatin molecules, the modified PLA (M-PLA-a = 87.1° ± 1.5°, M-PLA-b = 83.5° ± 1.4°) had smaller contact angle values than that of non-modified PLA (PLA-a = 108.6° ± 2.6°, PLA-b = 116.2° ± 3.1°), and that of the modified PGA (M-PGA-a = 79.3° ± 3.2°, M-PGA-b = 73.8° ± 1.8°) was smaller compared with that of the non-modified PGA (PGA-a = 98.2° ± 1.7°, PGA-b = 83.5° ± 1.4°). Based on the mechanical testing results, the tensile property and flexibility of samples increased slightly, and their swelling behavior also increased correspondingly. All the prepared samples exhibited non-toxicity with cell viability of more than 75%, and samples M-PGA-b presented the largest cell attachment ratios. In sum, this work exhibited great potential in the ACET application for juvenile pseudomyopia treatment.